Application of the spot color tone value at pharmaceutical tablet coating process control - Murillo-Fernández, Mac Arturo (2021)
A novel application of the SCTV (Spot Color Tone Value) formula from the graphic reproduction industry is proposed for the quality control of the pharmaceutical tablet coating process. Two procedures are analyzed: one by obtaining reflectance spectra, from which the chromatic attributes can be derived, and the other from obtaining the color coordinates of a calibrated photographic image. Our goal is to reduce the intervention, extraction and destruction of tablets during quality control, as well as simplify the control and evaluation of the process remotely, generating real-time responses for taking decisions.